AKUNTABILITAS HORIZONTAL DALAM PELAKSANAAN ALOKASI DANA DESA - Mita Widyastuti; Yayan Rudianto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2019)
The enactment of Law Number 6 of 2014 concerning Villages gives villages the authority to manage transfer funds from the National Government as regional allocations (ADD) and various other official sources. The village government is deemed capable of managing these funds based on planning, implementation, monitoring, and evaluation. As a consequence of the transfer funds, the village government is obliged to carry out accountability to the supra village government and the community to apply good governance norms. In general, the village has been able to carry out vertical accountability by giving accountability to the supra village government. However, as the smallest democratic autonomous region, the village head must carry out horizontal accountability; how is horizontal accountability implemented? This research is qualitative research with stakeholder informants in the village and takes Sukarapih village, Tambelang sub-district. Choosing Sukarapih village was based on the village's characteristics that experienced a transition from an agricultural village to a non-agricultural village. Due to it was close to the industrial environment of the Bekasi Regency.